Improving management of asthma: closing the loop or progressing along the audit spiral?. Issue 1 (March 1992) - Bucknall, C E; Robertson, C; Moran, F; Stevenson, R D
Abstract : OBJECTIVE--To assess whether the management of asthma has improved from three consecutive surveys. DESIGN--Retrospective case note survey of acute asthma admissions in 1983 and 1989; case notes selected from 1985-6 survey of prospectively identified patients to include only patients with a final discharge code of asthma. SETTING--A large city teaching hospital. Patients--101 patients with acute asthma as the primary diagnosis in 1983; 85 in 1985-6; and 133 in 1989, 14 of whom were subsequently transferred elsewhere. MAIN MEASURES--Conformity with a checklist of important aspects of the process of asthma management including initial assessment, treatment, supervision, and discharge and review arrangements. RESULTS--All patient groups were similar in age, smoking habit, and stay in hospital and, as an objective guide to severity of asthma, had similar initial pulse rates. Major improvements occurred in management: by 1989, 119(90%) patients were treated with oral corticosteroids (69(68%), 67(79%) in 1983, 1985-6 respectively) and 109(82%) with oxygen (62(61%), 51(60%)) (both p < 0.001). 114(86%) had regular recording of peak flow measurements (53(52%), 54(64%); p < 0.001), and 103/119(86%) were discharged taking oral corticosteroids (66(65%), 63(74%); p < 0.01). Significantly fewer patients, however, had their regular inhaled corticosteroid treatment increased on discharge (38/119(32%) v 53(52%), 39(46%); p < 0.01), but more were receiving high dose inhaled treatment on admission. CONCLUSIONS--The management of asthma improved significantly, and the normal practice of doctors has changed in an area of practice with longstanding problems.